2013
DOI: 10.1007/s12094-013-1014-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of microRNA-31 associates with aggressive tumor progression and poor prognosis in patients with bladder cancer

Abstract: These findings show that miR-31 may contribute to the progression of bladder cancer and its downregulation may be independently associated with unfavorable PFS and OS, suggesting that miR-31 might be a promising marker for further risk stratification in the treatment of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…Functional studies performed in cancer ce ll lines or animal models of various cancers suggest that, miRNAs can function as tumor suppressors, oncogenes, and regulate cancer pathways (Farazi et al, 2011). Aberrant expression of specific miRNAs has been reported in many tumor types 1 such as CRC, breast cancer, cervical cancer, non-small cell lung cancer, ovarian cancer and bladder cancer as well as being associated with patients' survival data, metastasis, and other clinicopathological factors (Toyama et al, 2012;Wan et al, 2012;Shen et al, 2013;Wang et al, 2013;Xiao et al, 2013;Liu et al, 2014;Xu et al, 2014). A previous study showed that miR-32 expression was upregulated in CRC tissues, and high expression was significantly correlated with the tumor stage, distal metastases and poor prognoses (Wu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies performed in cancer ce ll lines or animal models of various cancers suggest that, miRNAs can function as tumor suppressors, oncogenes, and regulate cancer pathways (Farazi et al, 2011). Aberrant expression of specific miRNAs has been reported in many tumor types 1 such as CRC, breast cancer, cervical cancer, non-small cell lung cancer, ovarian cancer and bladder cancer as well as being associated with patients' survival data, metastasis, and other clinicopathological factors (Toyama et al, 2012;Wan et al, 2012;Shen et al, 2013;Wang et al, 2013;Xiao et al, 2013;Liu et al, 2014;Xu et al, 2014). A previous study showed that miR-32 expression was upregulated in CRC tissues, and high expression was significantly correlated with the tumor stage, distal metastases and poor prognoses (Wu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer has diverse functional and biological characteristics, which include frequent recurrences and poor clinical outcome when tumor progresses to muscle invasive stage [14]. Numerous biomarkers and histopathological evaluation, such as tumor stage, tumor grade, and lymph node, have been investigated as prognostic indicators [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in a wide range of biological cellular functions, such as differentiation, apoptosis, and proliferation [3,6,12,14,21]. Additionally, the aberrant expression of miRNAs can be tracked in the pathogenesis, progression, and metastasis of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…재미있게도 miR-31은 다양한 암종 별로 그 발현 양상이 다르다고 알려져 있다. 방광암 [28,30], 유방암 [2,24,26], 식도암 [19], 난소암 [8], 전립선암 [3,10,27] 등에서는 miR-31의 발현이 저해되어 있다고 보고 되어있는 반면에 대장 암 [6,20,23,25,31], 폐암 [17,18] MicroRNA ( …”
Section: 법이 이용되고는 있으나 병의 진행에 관여하는 분자메커니즘 이해의 부족 때문에 여전히 완전한 치료는 어려운 실unclassified